Piranesi’s Letter to Lord Charlemont and the Public dated 20th June 1757 - Gavuzzo-Stewart, Silvia (Italogramma, 2020)
<span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*197.76px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927942);" role="presentation">There are only two copies known of this manuscript letter, both of which were <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*215.66px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.926893);" role="presentation">inserted by Piranesi in two sets of his <span dir="ltr" style="left: calc(var(--scale-factor)*294.50px); top: calc(var(--scale-factor)*215.66px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917508);" role="presentation">Antichità Romane <span dir="ltr" style="left: calc(var(--scale-factor)*384.94px); top: calc(var(--scale-factor)*215.66px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941529);" role="presentation">(1756), one of which <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*233.56px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924369);" role="presentation">is now in the Vatican Library, and the other in the Corsiniana Library in Rome. <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*251.46px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.980725);" role="presentation">They are almost identical, written in Italian with a French translation. This <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*269.36px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.913023);" role="presentation">indicates that Piranesi, despite the limited circulation of this manuscript, meant <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*287.25px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941732);" role="presentation">it to be read by international readers. The transcription (Appendix 1) and the <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*305.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93544);" role="presentation">translation into English (Appendix 2) given here are based on the Corsiniana <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*323.05px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.930948);" role="presentation">copy (53 K 19), to which I added paragraphs absent in the original. The letter <span dir="ltr" style="left: calc(var(--scale-factor)*108.00px); top: calc(var(--scale-factor)*340.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9096);" role="presentation">in the Vatican has been transcribed by Lamberto Donati (Donati 1950).